A Hybrid Channel Assignment Scheme in Large-Scale, Cellular-Structured Mobile Communication Systems - Kahwa, T.; Georganas, N. (IEEE transactions on communications, 1978)
This paper considers the problem of channel assignment in mobile communication systems, where the service area is divided in hexagonal cells. In particular, a Hybrid Channel Assignment Scheme is studied and certain results are obtained using GPSS simulation of a model 40-cell system.